Pengembangan Media Pop-Up Book untuk Memperkuat Karakter Nasionalisme pada Siswa Sekolah Dasar - Abda’u, Marissa Jenyo; Sofiana, Nina; Muhaimin, Muh (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to develop a pop up book media that can strengthen the character of nationalism in elementary school students. The development model used in this development research is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were all grade IV students of SDIT Ali Bin Abi Talib with a total of 34 people and 1 class teacher. Data were obtained from observation, interviews, documentation, and tests and analyzed quantitatively and qualitatively. The results showed that students needed pop-up book learning media to improve the character of nationalism. The pop-up book media developed gets a very valid category based on the validation results of each expert. The results of validation by material experts and media experts are included in the